2012
DOI: 10.1016/j.socscimed.2012.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of marital dissolution and mortality: Reevaluating the intersection of gender and age

Abstract: The study of marital dissolution (i.e. divorce and separation) and mortality has long been a major topic of interest for social scientists. We conducted meta-analyses and meta-regressions on 625 mortality risk estimates from 104 studies, published between 1955 and 2011, covering 24 countries, and providing data on more than 600 million persons. The mean hazard ratio (HR) for mortality in our meta-analysis was 1.30 (95% confidence interval [CI], 1.23-1.37) among HRs adjusted for age and additional covariates. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
93
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 158 publications
(108 reference statements)
13
93
1
3
Order By: Relevance
“…This is in line with other studies conducting in different populations that have demonstrated that employment is associated with the occurrence of heart disease [28] [29]. However, other predictors such as physical exercise, gender, and marital status were not found significant factors related to the heart disease that were not in line with other studies such as Kotecha et al, [30] who found that age and gender were predictors of heart disease and Rademaker et al, [31] found in their cohort study of 228 participants that gender is independently predictor for occurrence of coronary heart disease.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with other studies conducting in different populations that have demonstrated that employment is associated with the occurrence of heart disease [28] [29]. However, other predictors such as physical exercise, gender, and marital status were not found significant factors related to the heart disease that were not in line with other studies such as Kotecha et al, [30] who found that age and gender were predictors of heart disease and Rademaker et al, [31] found in their cohort study of 228 participants that gender is independently predictor for occurrence of coronary heart disease.…”
Section: Discussionsupporting
confidence: 93%
“…1 Married people have been consistently reported to be healthier than unmarried people, with more profound effects among men. [2][3][4][5][6][7] These associations can be attributed to both marital selection (ie, healthier people are more likely to be married) and marital protection (refers to the benefits of marital ties on health). [8][9][10][11] Consistent findings have been reported from research investigating marital transition (ie, a change in marital status during a given time period).…”
mentioning
confidence: 99%
“…[8][9][10][11] Consistent findings have been reported from research investigating marital transition (ie, a change in marital status during a given time period). 5 Men and women who experience marital transition by death or divorce have prospectively increased risk of associated onset and progression of cardiovascular disease. [12][13][14] The hypothesized mechanisms underlying the association between marital transition and cardiovascular risk include preexisting health conditions, 5 change to unhealthy profiles of health behavior, [15][16][17] poorer psychological state 2 stemming from the loss of financial stability, 18,19 and reduced social support and social networks 11,20 owing to loss of the spouse.…”
mentioning
confidence: 99%
See 2 more Smart Citations